2019
DOI: 10.1007/s00167-019-05491-6
|View full text |Cite
|
Sign up to set email alerts
|

Medial collateral ligament injuries of the knee in male professional football players: a prospective three-season study of 130 cases from the UEFA Elite Club Injury Study

Abstract: PurposeMedial collateral ligament (MCL) injury is the single most common traumatic knee injury in football. The purpose of this study was to study the epidemiology and mechanisms of MCL injury in men’s professional football and to evaluate the diagnostic and treatment methods used.MethodsFifty-one teams were followed prospectively between one and three full seasons (2013/2014–2015/2016). Individual player exposure and time-loss injuries were recorded by the teams’ medical staffs. Moreover, details on clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 31 publications
(40 reference statements)
4
54
0
Order By: Relevance
“…Future studies are warranted to also examine the accuracy of the diagnosis of LCL and PCL injuries among medical teams in men's professional football, as previously has been done for MCL injuries. 13 The injuries reported in this study were cases in which LCL or PCL injury was reported as the main diagnosis, ie, more LCL and PCL injuries may have occurred during the 17 seasons, with these injuries reported as concomitant injuries. Moreover, it is unknown how potentially concomitant injuries to the LCL or PCL injuries might have affected the outcome, since it is possible that players who sustained an LCL or PCL injury may have associated injuries in terms of meniscal or cartilage injuries.…”
Section: Limitationsmentioning
confidence: 89%
See 3 more Smart Citations
“…Future studies are warranted to also examine the accuracy of the diagnosis of LCL and PCL injuries among medical teams in men's professional football, as previously has been done for MCL injuries. 13 The injuries reported in this study were cases in which LCL or PCL injury was reported as the main diagnosis, ie, more LCL and PCL injuries may have occurred during the 17 seasons, with these injuries reported as concomitant injuries. Moreover, it is unknown how potentially concomitant injuries to the LCL or PCL injuries might have affected the outcome, since it is possible that players who sustained an LCL or PCL injury may have associated injuries in terms of meniscal or cartilage injuries.…”
Section: Limitationsmentioning
confidence: 89%
“…In most cases, the LCL and PCL injuries occurred predominantly during contact with another player or object, as has been described previously for MCL injuries. 13,14 Being tackled was the cause of approximately a quarter of the LCL injuries, while the most common contact mechanism for PCL was being kicked by another player. A contact mechanism as the most common cause of injury is different from ACL, where a non-contact mechanism is the most common.…”
Section: Injury Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…The results are also compared with the study performed by Lundblad et.al which showed that they had taken 4364 football players from 51 teams. Out of these players 130(3%) presented with MCL injuries 16 .…”
Section: Discussionmentioning
confidence: 99%